Large diffuse dwarfs in the dynamically cold triple galaxy systems - Karachentsev, I. D.; Nazarova, E. A.; Karachentseva, V. E.
We report on the discovery of three large diffuse dwarf (LDD) galaxies located in isolated triple systems. They have effective diameters of 3.6 ÷10.0 kpc and effective surface brightness of 26.2 ÷ 27.3 m/sq. arcsec. We note that the LDD galaxies tend to occur in small groups with a very low dispersion of radial velocities. The total (orbital) mass of the triplets approximately equals to their integral stellar mass within velocity measurement errors. The presence of LDD galaxies in cold multiple systems seems mysterious.
Keywords: Galaxies